A Sophisticated Approach towards a New Class of Copper(I)–Sulfur Cluster Complexes with Imidazolinium–Dithiocarboxylate Ligands. Issue 25 (5th July 2017) - Ortmeyer, Jochen; Flörke, Ulrich; Henkel, Gerald; Wilhelm, René; Neuba, Adam
Abstract : As a contribution to a better understanding of the coordination properties of imidazolinium–dithiocarboxylate ligands towards copper, the first route towards oligonuclear copper–betaine complexes has been developed. Treatment of the coordination polymer [CuCl(Bz2 ImCS2 )] n (1 ) suspended in acetonitrile with thallium(I) hexafluorophosphate in different ratios affords the discrete copper(I) cluster cations [Cu4 (Bz2 ImCS2 )4 Cl2 ] 2+ (2 ) and [Cu3 (Bz2 ImCS2 )5 ] 3+ (3 ). Single‐crystal X‐ray diffraction of2 (PF6 )2 · 2MeCN and3 (PF6 )3 · 2MeCN· Et2 O reveals the occurrence of unique copper–sulfur architectures. The Cu–S/Cl skeleton of2 contains two elongated trigonal‐prismatic Cu4 S2 entities which share a common Cu4 face. In contrast, the Cu atoms of3 define an isosceles triangle. Both compounds exhibit distorted tetrahedral copper coordination sites, based on S3 Cl (within2 ) and S4 (within3 ) donor sets, and host dithiocarboxylate zwitterions in each of two different coordination modes. Overall, three different types of binding principles towards copper are presented here. Abstract : Two different discrete copper(I) cluster cations, [Cu4 (Bz2 ImCS2 )4 Cl2 ] 2+ and [Cu3 (Bz2 ImCS2 )5 ] 3+, were synthesized by decomposition of the coordination polymer [CuCl(Bz2 ImCS2 )2 ] n through the elimination of chloride ions. These are the first structurally characterized oligonuclear copper–betaine compounds with unique copper–sulfur architectures built up from imidazolinium–dithiocarboxylate ligands.